2017
DOI: 10.1007/978-3-319-89794-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in Ionic Liquids: Current Status of Experiments and Simulations

Abstract: In the last two decades, while searching for interesting applications of ionic liquids as potent solvents, their solvation properties and their general impact on biomolecules, and in particular on proteins, gained interest. It turned out that ionic liquids are excellent solvents for protein refolding and crystallization. Biomolecules showed increased solubilities and stabilities, both operational and thermal, in ionic liquids, which also seem to prevent self-aggregation during solubilization. Biomolecules can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 125 publications
2
51
0
Order By: Relevance
“…Ionic liquids interact with various hydrophilic and hydrophobic amino acids of a protein through an intricate balance of hydrogen bonds, disulfide bridges, hydrophobic effects, and ionic interactions (48). When mixed with other liquids such as water, a more complex interplay between ions occurs that, depending on the nature of ions, can result in formation of micelles or microemulsions (48). A prolonged and higher oral plasma concentration of poorly water-soluble drugs dispersed in ILs was also reported by Williams et al (32).…”
Section: Discussionmentioning
confidence: 99%
“…Ionic liquids interact with various hydrophilic and hydrophobic amino acids of a protein through an intricate balance of hydrogen bonds, disulfide bridges, hydrophobic effects, and ionic interactions (48). When mixed with other liquids such as water, a more complex interplay between ions occurs that, depending on the nature of ions, can result in formation of micelles or microemulsions (48). A prolonged and higher oral plasma concentration of poorly water-soluble drugs dispersed in ILs was also reported by Williams et al (32).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallization supported by bare membrane (IL-HCM 0) and by standard plastic sitting-drop cradle (REF) was carried out for comparison (see Section 2.2). Among proteins usually used for testing new crystallization methods or screenings, we have chosen GI, whose crystallization in standard conditions, in the presence of ILs as additives [7] and of hydrogels [28], is well known.…”
Section: Glucose Isomerase Crystallization By Using Il-hcmsmentioning
confidence: 99%
“…Simulations have shown that the concentration of cations at the protein surface exceeds that of anions, since cations do not contribute to the anionic hydrogen-bonded network with water. Excess cations interact with the protein surface at negatively charged areas, through strong Coulomb interactions, and at non-polar surface areas, through dispersion interactions mediated by their alkyl chains [7]. Instead anions strongly interact with positively charged areas through hydrogen bonds and Coulomb interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations